Pendampingan Certified Canteen Pada Paguyuban Pedagang Cafetaria Universitas Muhammadiyah Ponorogo sebagai Salah Satu Upaya Pendukung Internasionalisasi Kampus - Fery Setiawan; Elok Putri Nimasari; Azis Akbar Ramadhan; Niken Hilvanda Putri (LPPM ITB AAS Indonesia Surakarta, 2025)
This community service program involves a series of interactive socialization to traders who are members of the cafeteria traders association at Muhammadiyah University of Ponorogo as a service partner which includes material on the introduction of halal certification, halal certification stages, brand legality and product branding. The main focus of this service is halal certification which is provided to help service partners as traders who are members of the cafeteria traders association at Muhammadiyah University of Ponorogo in ensuring that food, beverage and other consumer goods do not contain haram ingredients and are processed according to Islamic law, helping consumers especially students and students of Muhammadiyah University of Ponorogo feel safe and comfortable in consuming these products. In addition, product branding is needed by partners in facing the challenges of business competition, especially product marketing in the increasingly competitive era of globalization, then brand legality is needed so that each partner's product has legal protection and branding strengthening. Through an inclusive and community-based approach, it is hoped that partners as traders who are members of the cafeteria traders association at Muhammadiyah University of Ponorogo can be more empowered and educated. The implementation method involved identifying public complaints, identifying problems, planning, implementing, evaluating, and following up. The results of this community service program demonstrated a significant increase in the knowledge of participating partners and their ability to access and utilize digital services for halal certification registration. Thus, this community service program not only contributes to individual empowerment but also strengthens partners as a whole in their pursuit of social welfare and justice. Keywords: Halal Certification, Traders, Muhammadiyah University of Ponorogo